PENGARUH PENAMBAHAN AIR REBUSAN KENTANG (Solanum tuberosum L.), BAP DAN NAA TERHADAP INDUKSI TUNAS JATI EMAS (Cordia subcordata) SECARA IN VITRO - Imanudin (FP AGRO 16 UMY 021, 2016)
This research aimed to know the influence of boiedl water potato combinedwith Benzyl Amino Purin and Naphtalene Acetic Acid in inducing shoot of golden teak in vitro. This research was held in laboratory in vitro culture, Faculty of Agriculture Universitas Muhammadiyah Yogyakarta on February until April 2016. This research used single factor experimental method, with five treatments which consist of BAP(0,5;,1,0;,1,5;,2,0; 2,5 mg/l), NAA( 0.1;,0,2;,0,3;, 0,4;, 0,5 mg/l) and boiled water potato(100, 200, 300, 400, 500 ml/l).The parameter observed were are percentage of contamination, percentage of Browning, percentage of life and number of shoot bud. The result showed that the addition of boiled water potato 300 ml/l + BAP 1,5 mg/l and NAA 0,3 mg/l was the best treatment as shown by the parameter highest shoot (40,66) on the 8th week, the percentage explant of life (90%), the percentage explant of contamination (10%), the percentage explants of Browning (30%) and the percentage explant of recovery (30%). Keywords: Golden teak (Cordia subcordata), BAP and NAA, Boiled Water Potato